Transaction Costs in Resource Redeployment for Multi-niche Firms - Giarratana, Marco; Santaló, Juan (Informs PubsOnline, 2020)
Transaction costs strongly influence diversification dynamics, as predicted by resource theory. A mainstream view links the profitability of diversification with the existence of transaction costs that prevent a firm from trading in fungible, scale-free resources. This study applies a neo-Penrosian perspective to transaction costs, with the notion that diversification may be driven by the redeployment of non-scale-free resources. An empirical analysis, using tax changes in the drink sector as a measure of exogenous demand variation, offers results consistent with the prediction that redeployment is particularly relevant when retailing is concentrated and single-product competition within a focal product niche (e.g., beer) is fragmented. This study also measures redeployment across a portfolio of a multiniche firm when changes in its sales-growth rates for a particular product niche might imply contrasting changes in other product niches. The resulting evidence is consistent with predictions that demand uncertainty, and transaction costs create viable
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura